Immunogenicity of TNF-Inhibitors - Atiqi, Sadaf; Hooijberg, Femke; Loeff, Floris C.; Rispens, Theo; Wolbink, Gerrit J. (Frontiers in Immunology, 2020)
Tumor necrosis factor inhibitors (TNFi) have significantly improved treatment outcome of rheumatic diseases since their incorporation into treatment protocols two decades ago. Nevertheless, a substantial fraction of patients experiences either primary or secondary failure to TNFi due to ineffectiveness of the drug or adverse reactions. Secondary failure and adverse events can be related to the development of anti-drug antibodies (ADA). The earliest studies that reported ADA towards TNFi mainly used drug-sensitive assays. Retrospectively, we recognize this has led to an underestimation of the amount of ADA produced due to drug interference. Drug-tolerant ADA assays also detect ADA in the presence of drug, which has contributed to the currently reported higher incidence of ADA development. Comprehension and awareness of the assay format used for ADA detection is thus essential to interpret ADA measurements correctly. In addition, a concurrent drug level measurement is informative as it may provide insight in the extent of underestimation of ADA levels and improves understanding the clinical consequences of ADA formation. The clinical effects are dependent on the ratio between the amount of drug that is neutralized by ADA and the amount of unbound drug. Pharmacokinetic modelling might be useful in this context. The ADA response generally gives rise to high affinity IgG antibodies, but this response will differ between patients. Some patients will not reach the phase of affinity maturation while others generate an enduring high titer high affinity IgG response. This response can be transient in some patients, indicating a mechanism of tolerance induction or B-cell anergy. In this review several different aspects of the ADA response towards TNFi will be discussed. It will highlight the ADA assays, characteristics and regulation of the ADA response, impact of immunogenicity on the pharmacokinetics of TNFi, clinical implications of ADA formation, and possible mitigation strategies.